Targeting microRNAs to Regulate the Integrity of the Blood–Brain Barrier - Wang, Juntao; Xu, Fang; Zhu, Xiaoming; Li, Xianghua; Li, Yankun; Li, Jia (Frontiers in Bioengineering and Biotechnology, 2021)
The blood-brain barrier (BBB) is a highly specialized neurovascular unit that protects the brain from potentially harmful substances. In addition, the BBB also engages in the exchange of essential nutrients between the vasculature and brain parenchyma, which is critical for brain homeostasis. Brain diseases, including neurological disorders and cerebrovascular diseases, are often associated with disrupted BBB integrity, evidenced by increased permeability. Therefore, defining the mechanisms underlying the regulation of BBB integrity is crucial for the development of novel therapeutics targeting brain diseases. MicroRNAs (miRNA), a type of small non-coding RNAs, are emerging as an important regulator of BBB integrity. Here we review recent developments related to the role of miRNAs in regulating BBB integrity.